Evaluating the Safety of Retrograde Intrarenal Surgery (RIRS): Intra- and Early Postoperative Complications in Patients Enrolled in the Global Multicentre Flexible Ureteroscopy Outcome Registry (FLEXOR) - TANIDIR, YILÖREN (My University, 2024)
PURPOSE: To assess the incidence of the most common intra- and early postoperative complications following RIRS in a large series of patients with kidney stones. METHODS: We conducted a retrospective analysis of patients with kidney stones who underwent RIRS across 21 centers from January 2018 to August 2021, as part of the Global Multicenter Flexible Ureteroscopy Outcome (FLEXOR) Registry. RESULTS: Among 6669 patients undergoing RIRS, 4.5% experienced intraoperative pelvicalyceal system bleeding without necessitating blood transfusion. Only 0.1% of patients, required a blood transfusion. The second most frequent intraoperative complication was ureteric injury due to the ureteral access sheath requiring stenting (1.8% of patients). Postoperatively, the most prevalent early complications were fever/infections requiring antibiotics (6.3%), blood transfusions (5.5%), and sepsis necessitating intensive care unit admission (1.3%). In cases of ureteric injury, a notably higher percentage of patients exhibited multiple stones and stone(s) in the lower pole, and these cases were correlated with prolonged lasing and overall surgical time. Hematuria requiring a blood transfusion was associated with an increased prevalence of larger median maximum stone diameters, particularly among patients with stones exceeding 20 mm. Furthermore, these cases exhibited a significant prolongation in surgical time. Sepsis necessitating admission to the intensive care unit was more prevalent among the elderly, concomitant with a significantly larger median maximum stone diameter. CONCLUSIONS: Our analysis showed that RIRS has a good safety profile but bleeding requiring transfusions, ureteric injury, fever, and sepsis are still the most common complications despite advancements in technology.
Keywords: Tıp; Sağlık Bilimleri; Temel Tıp Bilimleri; Medicine; Health Sciences; Fundamental Medical Sciences; Klinik Tıp (MED); Klinik Tıp; TIP, GENEL & DAHİLİ; Clinical Medicine (MED); CLINICAL MEDICINE; MEDICINE, GENERAL & INTERNAL; Genel Tıp; General Medicine; Hematuria; Kidney Calculi; Sepsis